(untitled) (Journal of Oriental Studies, 2017)
The article considers a definition of the main features of the lexicographical work “Diuan al-Adab” as an explanatory Arabic dictionary of the famous representative of the Arab classical philology Ishaq al-Farabi. The features of the compilation methods are analyzed, which appeared in the new Arabic lexicography in the epoch, as well as there is designated reformism of the author in this field. The article explains advantages of the new method, which determinate a point of tractate among similar pieces of work.